Analisis Kompetensi dan Gaya Kepemimpinan Pengaruhnya Terhadap Motivasi Serta Dampaknya Terhadap Kinerja Pegawai - Yunan Surono; Jonner Simarmata; Albetris Albetris; Azizah Azizah; Heni Pratiwi; Dandy Berlian; Zuhri Saputra Hutabarat (Jurnal Ekonomi Bisnis, Manajemen dan Akuntansi (JEBMA), 2023)
This research is to analyze the influence of competency aspects and leadership style on motivation and its impact on employee performance. This research uses descriptive and verification analysis methods. Descriptive analysis is used to describe the characteristics of respondents and research variables without testing. Verifiability analysis is used to determine the magnitude of the influence of the independent variable on the dependent variable. This research uses all employees at the Jambi Province Transportation Service. Apart from that, the data used in this research is primary data obtained from the results of the questionnaire given and filled in by each employee. The data analysis technique used is path analysis, with the help of the SPSS version 22.0 software program. The results of the research show that competency and leadership style through motivation simultaneously and partially have a positive effect on the performance of Jambi Province Transportation Service employees and there is a direct and indirect influence of competence and leadership style through motivation on the performance of Jambi Province Transportation Service employees. So it can be concluded that the competency, leadership style, motivation and performance of employees at the Jambi Province Transportation Service are still relatively good.